2014
DOI: 10.1038/ncomms4506
|View full text |Cite
|
Sign up to set email alerts
|

Local translation of TC10 is required for membrane expansion during axon outgrowth

Abstract: The surface of developing axons expands in a process mediated by the exocyst complex. The spatial-temporal regulation of the exocyst is only partially understood. Here we report that stimulated membrane enlargement in dorsal root ganglion (DRG) axons is triggered by intra-axonal synthesis of TC10, a small GTPase required for exocyst function. Induced membrane expansion and axon outgrowth are inhibited after axon-specific knockdown of TC10 mRNA. To determine the relationship of intra-axonal TC10 synthesis with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 57 publications
(99 reference statements)
2
58
0
Order By: Relevance
“…The requirement for protein synthesis and degradation is strikingly similar to the requirements for axon elongation and growth cone turning in response to attractive guidance cues [7], and a comparison of the axonal mRNA pools present in uninjured matured and actively regeneration axons of cortical neurons revealed that axotomy triggers the recruitment of transcripts related to axonal targeting [40]. Importantly, while some of the axonally localized mRNAs have been shown to support axon outgrowth and elongation in response to attractive cues, such as β-actin [9,11], Par3 [12], and TC10 [13], the translation of others, including RhoA [8] and cofilin [10], leads to growth cone collapse and axon retraction. Therefore, the axonally localized transcriptome in severed nerves might support the innate regenerative capacity of injured axons but at the same time also mediate the growth preventing effects from the inhibitory molecules in the nerve scar and myelin that ultimately prevent regenerative growth.…”
Section: Regeneration After Nerve Injurymentioning
confidence: 83%
See 4 more Smart Citations
“…The requirement for protein synthesis and degradation is strikingly similar to the requirements for axon elongation and growth cone turning in response to attractive guidance cues [7], and a comparison of the axonal mRNA pools present in uninjured matured and actively regeneration axons of cortical neurons revealed that axotomy triggers the recruitment of transcripts related to axonal targeting [40]. Importantly, while some of the axonally localized mRNAs have been shown to support axon outgrowth and elongation in response to attractive cues, such as β-actin [9,11], Par3 [12], and TC10 [13], the translation of others, including RhoA [8] and cofilin [10], leads to growth cone collapse and axon retraction. Therefore, the axonally localized transcriptome in severed nerves might support the innate regenerative capacity of injured axons but at the same time also mediate the growth preventing effects from the inhibitory molecules in the nerve scar and myelin that ultimately prevent regenerative growth.…”
Section: Regeneration After Nerve Injurymentioning
confidence: 83%
“…Only at the beginning of this century did work by Holt's group conclusively demonstrate that local protein synthesis is required for the chemotropic responses of axons to attractive and repulsive guidance cues [7]. This work heralded an extremely productive phase of research on local translation in developing axons, and now intra-axonal protein synthesis is recognized to be crucial for growth cone behavior [7][8][9][10][11][12][13][14], axonal pathfinding [15][16][17], axon maintenance [18], and retrograde signaling in developing axons [19,20]. However, far less is known about the extent and importance of localized protein synthesis in axons after the developmental period.…”
Section: Intra-axonal Protein Synthesismentioning
confidence: 99%
See 3 more Smart Citations